2018
DOI: 10.5336/dentalsci.2018-61371
|View full text |Cite
|
Sign up to set email alerts
|

Oral Aspects in Children with Nephrotic Syndrome

Abstract: Oral Aspects in Children with Nephrotic Syndrome A AB BS ST TR RA AC CT T O Ob bj je ec ct ti iv ve e: : Nephrotic syndrome (NS) is caused by different disorders that damage the kidneys. This damage leads to the excessive release of protein into the urine. Due to alterations in mineral metabolism in young patients with nephrotic syndrome, dental development, periodontal tissues, and alveolar bone may be disturbed. The aim of this study was to assess the oral health status in children with nephrotic syndrome an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 18 publications
(28 reference statements)
1
9
0
Order By: Relevance
“…This study showed some lower caries experience in the iNS participants compared to healthy ones (83.0% vs 95.7%). Like Güzel et al [17] in pediatric patients with nephrotic syndrome in remission phase, we found some lower dmft and DMFT values in iNS patients compared to the controls. On the contrary, another study presented significantly higher dmft and slightly lower DMFT values compared to the controls [16].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This study showed some lower caries experience in the iNS participants compared to healthy ones (83.0% vs 95.7%). Like Güzel et al [17] in pediatric patients with nephrotic syndrome in remission phase, we found some lower dmft and DMFT values in iNS patients compared to the controls. On the contrary, another study presented significantly higher dmft and slightly lower DMFT values compared to the controls [16].…”
Section: Discussionsupporting
confidence: 81%
“…However, another study showed that only 1 out of 38 patients (i.e. 2.6%) was affected by enamel hypoplasia [17].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Oral hygiene practice among children with PNS has been reported as poorer than among healthy controls [10], with significantly increased food debris and dental plaque [8,11]. Despite not providing specific calculus indices, two studies by Babu and Jana (2014) [12] and Subramaniam (2012) [8] revealed a high incidence of calculus, especially at the lingual surface of mandibular incisors, in children with PNS.…”
Section: Introductionmentioning
confidence: 99%
“…Even though poor oral care is well known as a risk factor for caries [8,12], the association between dental caries and PNS is, however, inconsistent in the literature. Several studies [7,14] revealed a significantly higher percentage of dental caries in NS children than in controls, while no difference [11,15] or contrastive results [8,10,12] were also reported.…”
Section: Introductionmentioning
confidence: 99%